Diverging Water Ages Inferred From Hydrodynamics, Hydrochemical and Isotopic Tracers in a Tropical Andean Volcano-Sedimentary Confined Aquifer System - Manciati, Carla; Taupin, Jean Denis; Patris, Nicolas; Leduc, Christian; Casiot, Corinne (Frontiers in Water, 2021)
Hydrogeology in the Andes cordillera reflects its complex geological history. In most cases, groundwater flows through fractures and faults that compartmentalize the volcanic material, and through the primary porosity of the volcano-sedimentary material. The volcanic mineral context and geothermal environment mark the groundwater chemistry, especially in the high concentrations of specific trace elements. This study focuses on the complex system of the Tumbaco – Cumbayá – Los Chillos aquifer, in the vicinity of the Ilaló volcano near Quito (Ecuador). Hydrodynamic, geochemical and isotopic tools were used to assess the chemical characteristics of water and its origin, identify the recharge areas, and estimate the transit time of water using simple methods and scarce data. Results revealed two distinct aquifers, one in the volcanic cone located in the center of the study area, and the other in the volcano-sedimentary series of the Tumbaco – Cumbayá – Los Chillos valley. The volcanic aquifer is characterized by a high mineralization, a recharge zone between 2400 m asl and 3100 m asl, and radiocarbon concentrations lower than 20 pmc. The volcano-sedimentary aquifer seems to behave as a partly disconnected system, between the north and the south of Ilaló volcano, and also with a great heterogeneity, maybe due to the presence of lenses of volcanic ash. It has an intermediate mineralization, a mean recharge zone between 2300 and 2700 m asl, and 14C activities between 45.4 and 87.4 pmc in apparent contradiction with the hydrodynamic mass balance.